2016
DOI: 10.1002/jnr.23986
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes, hormesis, and antioxidants in neuroinflammation: Role of NRLP3 in Alzheimer disease

Abstract: Alzheimer disease (AD) is a progressive neurodegenerative disorder leading to cognitive decline, neuropsychiatric symptoms, disability, caregiver burden, and premature death. It represents the most prevalent cause of dementia, and its incidence rates exponentially increase with increasing age. The number of Americans living with AD is rapidly increasing. An estimated 5.4 million Americans of all ages have AD in 2016. One in nine people aged 65 and older has AD, and by midcentury, someone in the United States w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(75 citation statements)
references
References 148 publications
(172 reference statements)
0
68
0
Order By: Relevance
“…Of all inflammasomes, the NLRP3 inflammasome is the most important member. NLRP3 inflammasome is a component of the innate immune system which can promote the maturation of pro-inflammatory cytokines IL-1β and IL-18, thus initiating inflammatory responses (21). In fact, several studies found that the assembly of NLRP3 inflammasome, the activation of caspase-1 and the release of IL-1β and IL-18 during TBI, indicating NLRP3 was involved in TBI pathology (8,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Of all inflammasomes, the NLRP3 inflammasome is the most important member. NLRP3 inflammasome is a component of the innate immune system which can promote the maturation of pro-inflammatory cytokines IL-1β and IL-18, thus initiating inflammatory responses (21). In fact, several studies found that the assembly of NLRP3 inflammasome, the activation of caspase-1 and the release of IL-1β and IL-18 during TBI, indicating NLRP3 was involved in TBI pathology (8,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, astrocytes, neurons, brain pericytes, T cells and mast cells also play a significant role in the brain inflammatory mechanisms. Inflammatory mediators, neurotoxic mediators, inflammasomes and hormones released by the activated glial cells and injured neurons are involved in neuroinflammation in AD and PD pathogenesis (Tufekci et al, 2012; Pennisi et al, 2016; Becher et al, 2017; Gualtierotti et al, 2017; Rustenhoven et al, 2017; Sawikr et al, 2017; Song et al, 2017). Substantia nigra has the highest density of microglial cells, which are found, to be activated in PD brains.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is a multifaceted, progressive neurodegenerative disease that includes several detrimental processes in the brain: neuroinflammation (Calsolaro & Edison, 2016;Pennisi et al, 2017); neurotransmitter system dysregulation (Correia, Perry, & Moreira, 2016); increased oxidative stress (Calabrese et al, 2018;Pennisi et al, 2017) and glucose and energy metabolism dysfunction (Abolhassani et al, 2017;Duran-Aniotz & Hetz, 2016). All of these impairments result in the accumulation of amyloid-beta (Aβ) and other misfolded proteins (Lithfous, Dufour, & Després, 2013).…”
Section: Introductionmentioning
confidence: 99%